City of Caesar, City of God - Klein, Konstantin; Wienand, Johannes (2022)
This volume explores the entangled history of Constantinople and Jerusalem in Late Antiquity. The two cities were powerful symbols of Empire and Church, interconnected and interdependent in multiple ways. Covering the transition between Antiquity, Byzantium, and the Middle Ages, distinguished international scholars investigate art, ceremony, religion, ideology, and imperial rule in these vibrant, inspiring and fascinating urban hubs.